Natural Dye and Ink Used in Book Arts - ZOR, Züleyha (MAS Journal of Applied Sciences, 2023)
All societies take their place on the stage of history with their cultural heritages such as language, history and art. In ancient civilizations, it is seen that beliefs and sacred values play a major role while works of art gain their own identity. These beliefs shaped Turkish art in the Central Asian nomadic culture, namely, the belief in the Sky God and Shamanism, Manichaeism and Buddhism during the Uyghurs period, and then Islam. Carpet-rug and fabric decoration arts, book arts, architecture, literature and musical arts are seen to be prominent in Turkish art. Book arts, the effort to write the Qur’an and bring together the written pages in the first years of Islam gave way to the effort to write and decorate the holy book better in the following years. Thus, the importance and importance given to the Islamic faith by the Turkish society after accepting Islam enabled them to progress in the arts of books and to create magnificent works. Book arts; It covers all the arts of calligraphy, illumination, miniature, marbling and bookbinding. The basic materials such as paint, paper and ink used while performing these arts were obtained from completely natural products. Perhaps the most important reason why the calligraphy plates of the miniatures and illuminations made hundreds of years ago have survived to the present day without deterioration, is that they are made of natural materials. Today, it is not known whether the chemical materials used while performing these arts will last for hundreds of years. In this study; It is aimed to give information about how the natural dye and ink used in the field of book arts in the past centuries were obtained. For this purpose, a literature review was conducted and the opinions of expert artists were consulted about how the used substances were obtained.